2009
DOI: 10.1208/s12249-009-9313-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Shape on Dry Particle Inhalation: Study of Flowability, Aerosolization, and Deposition Properties

Abstract: Abstract. The shape effects of dry particles on flowability, aerosolization, and deposition properties in inhalation drug delivery are studied. The properties are compared with similar size range particles of different shapes such as sphere, needle, cube, plate, and pollen. Flowability of the particles is characterized by Carr's compressibility index and angle of slide (θ) method. The aerosolization and deposition properties of the particles are studied in vitro using an eight-stage Anderson cascade impactor w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(91 citation statements)
references
References 28 publications
1
88
0
2
Order By: Relevance
“…The tap density decreases as the particle shape deviates more and more from the sphere [42]. Experimental studies indeed showed that the tap density of spheres has the highest value while the needle-shaped particles had the lowest tap density among cylinder, cube and needleshaped particles [43,44].…”
Section: Tap Densities Of Limnpo 4 and Its Compositesmentioning
confidence: 99%
“…The tap density decreases as the particle shape deviates more and more from the sphere [42]. Experimental studies indeed showed that the tap density of spheres has the highest value while the needle-shaped particles had the lowest tap density among cylinder, cube and needleshaped particles [43,44].…”
Section: Tap Densities Of Limnpo 4 and Its Compositesmentioning
confidence: 99%
“…They can also penetrate deeply into body organs and remain in the body for a long time (Balasubramanian et al 2010). It has been shown that the morphology of the soot agglomerates plays an important role in their effects on climate (Scarnato et al 2013) and human health (Hassan and Lau 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, a shape-dependent difference in aerosol deposition pattern was observed. Previous report has shown that elongated and pollen-shaped particles tend to exhibit better flowability and higher FPF than spherical particles (40). This is because elongated particles have longer suspended time in the air and can travel further in the lung airways (40).…”
Section: Discussionmentioning
confidence: 97%